Addressing Labour Market Duality in Korea - Grubb, David (OECD Social, Employment and Migration Working Papers, 2007)
The Korean labor market has created many jobs over the past several decades, accompanying rapid economic growth. More recently, this favorable job performance has gone hand-in-hand with a rapid increase of temporary employment and other flexible or atypical work arrangements (usually called "non-regular" work in Korea. This trend has raised much concern in Korean society about the risk of persistent labor market duality and the various downsides associated with such a development...